Perancangan Sistem Manajemen Pergudangan di PT. Intidaya Dinamika Sejati - Daniel Wahyuning Laksono; Herry Christian Palit (Jurnal Titra, 2023)
PT. Intidaya Dinamika Sejati is a workshop company as well as the official holder for importers of blowers and vacuums in Indonesia with Pedro Gil and Becker as its brands. As a company that has a vision and mission to become a public company, it is appropriate to need a stable system that has a concept of continuous improvement to support success. This research began with the purchase of goods which are always processed even though the availability of goods was adequate, the cause of this incident was the difference in the physical stock in the warehouse with the stock recorded in the system. The purpose of this research was none other than to find out the root cause of the problem from the incompatibility of recording and storage data. The research was conducted by observation method. The results of the study stated that the discrepancy was caused by logistics management and warehouse management that lacked discipline both from the operational and warehouse management side, which resulted in discrepancies in the recording results. Through the results of the analysis, it is found a suggestion in the form of using the bar code method which includes rearranging the storage system, updated operating standards, and an organized recording method. From the result, it is expected to provide a concept that can be implemented and as a support in the company development process.